2010
DOI: 10.1089/neu.2010.1315
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Patients with Severe Traumatic Brain Injury Who Have Glasgow Coma Scale Scores of 3 or 4 and Are Over 65 Years Old

Abstract: The goal of this study was to investigate the outcomes of patients with traumatic brain injury (TBI) who had Glasgow Coma Scale (GCS) scores of 3 or 4, and were aged 66 years or older. Between January 2001 and December 2005, 13 European centers enrolled patients with severe brain trauma. Data sets of all patients who had a GCS score of 3 or 4 and were 66 years of age or older were analyzed. Outcomes were classified according to the Glasgow Outcome Scale (GOS) 12 months post-trauma as "favorable" (GOS score of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(52 citation statements)
references
References 35 publications
3
47
0
2
Order By: Relevance
“…Factors that are associated with poor survival include hypoxia, extremes of age, hypotension, hypercarbia, hyperglycemia, mechanism of injury, and hypothermia. 6,21,25,28,36,39,43,51,53 Other factors that may be independent predictors of outcome in severe TBI patients include prehospital deterioration, duration of coma, time to "follow commands" duration of amnesia, time to resume oral feeding, and measurement of the efficacy of interventions designed to lower ICP. 17,20,40,45 As most of the published studies evaluated adults, we sought to examine a relatively large cohort of children presenting with a postresuscitation GCS (modified for pediatric patients) score of 3 or 4.…”
Section: Discussionmentioning
confidence: 99%
“…Factors that are associated with poor survival include hypoxia, extremes of age, hypotension, hypercarbia, hyperglycemia, mechanism of injury, and hypothermia. 6,21,25,28,36,39,43,51,53 Other factors that may be independent predictors of outcome in severe TBI patients include prehospital deterioration, duration of coma, time to "follow commands" duration of amnesia, time to resume oral feeding, and measurement of the efficacy of interventions designed to lower ICP. 17,20,40,45 As most of the published studies evaluated adults, we sought to examine a relatively large cohort of children presenting with a postresuscitation GCS (modified for pediatric patients) score of 3 or 4.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, increasing age is strongly associated with a poor prognosis both in experimental trauma models and following TBI in humans (Livingston et al, 2005;Onyszchuk et al, 2008;Rothweiler et al, 1998;Sendroy-Terrill et al, 2010;Susman et al, 2002). Confirmed factors of poor prognosis for patients with GCS 3 or 4 and older than 65 years are closed basal cisterns and midline shift > 15 mm on the first CT (Brazinova et al, 2010). The worse outcomes in elderly human subjects occur despite what appears to be less severe TBI, as measured by a higher GCS upon admission (Livingston et al, 2005;Susman et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…3,6,7,13 Sorrentino et al 25 found differences in cerebral autoregulation and cerebral pressure reactivity index in elderly patients with TBI. However, there is also evidence that older patients may be more responsive to intracranial hypertension treatment.…”
Section: Factors Influencing the Decision To Monitormentioning
confidence: 99%